Full 3D Plant Reconstruction via Intrusive Acquisition - Yin, Kangxue; Huang, Hui; Long, Pinxin; Gaissinski, Alexei; Gong, Minglun; Sharf, Andrei (Computer graphics forum, 2016)
Digitally capturing vegetation using off‐the‐shelf scanners is a challenging problem. Plants typically exhibit large self‐occlusions and thin structures which cannot be properly scanned. Furthermore, plants are essentially dynamic, deforming over the time, which yield additional difficulties in the scanning process. In this paper, we present a novel technique for acquiring and modelling of plants and foliage. At the core of our method is an intrusive acquisition approach, which disassembles the plant into disjoint parts that can be accurately scanned and reconstructed offline. We use the reconstructed part meshes as 3D proxies for the reconstruction of the complete plant and devise a global‐to‐local non‐rigid registration technique that preserves specific plant characteristics. Our method is tested on plants of various styles, appearances and characteristics. Results show successful reconstructions with high accuracy with respect to the acquired data. Digitally capturing vegetation using off‐the‐shelf scanners is a challenging problem. Plants typically exhibit large self‐occlusions and thin structures which cannot be properly scanned. Furthermore, plants are essentially dynamic, deforming over the time, which yield additional difficulties in the scanning process. In this paper, we present a novel technique for acquiring and modelling of plants and foliage. At the core of our method is an intrusive acquisition approach, which disassembles the plant into disjoint parts that can be accurately scanned and reconstructed offline.